« L'enfant philosophe ? » - Jean-Marc Lamarre (Nantes Université, 2012)
Can the discussions between pupils be regarded as philosophical discussions, at primary school? Can child attain philosophy? According to the author, the discussions "with philosophical aim", as they are called, prepare children for philosophy but, strictly speaking, they are not philosophical ; connected with interpretative debates and classmates life debates, they contribute to the development of the person and of the citizen by virtue of exercising the deliberate thinking. Children think but any awakening of the deliberate thinking can not be called "philosophy". The author removes the frequent confusion between thought and philosophy in showing that there is some thought (in the strong sense of the word : a thought capable of truth) in sciences, arts, literature, politics. As philosophy is characterized by an aim for totalizing, systemizing and radicalizing, the child has got neither the concepts nor the culture nor the human experience which would make it possible for him to enter philosophy. It is in the adolescence that a threshold which makes the philosophy learning possible is crossed. Which thought process is at work in the discussions at primary school? The author considers that these discussions are a kind of devices of thought learning, according to the three Kantian maxims of the common sense : to think by oneself (go beyond the immediate opinions), to think in putting oneself in another one's place (widen one's opinion), to think in agreement with oneself (think in a consistent way). These discussions must be situated in the constructive scope of the moral and civic education.